In Vitro Effect Of Cow Urine Distillate And Its Synergistic Action With Aqueous Polyherbal Extract On Lymphoblastogenesis In Commercial Layer Chicks - Jivani, Bhavisha M.; Fefar, D.T.; Joshi, B.P.; Ghodasara, D.J.; Patel, Nikita J.; Ghodasara , Priya D. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The present investigation was undertaken to study in vitro effect of cow urine distillate and its synergistic action with aqueous polyherbal extract containing Ocimum sanctum (Tulsi), Tinospora cordifolia (Guduchi) and Withania somnifera (Ashwagandha) on lymphoblastogenesis in commercial layer chicks. A total of 270, day old BV-300 layer chicks were randomly divided into nine groups comprising 30 chicks in each group. Group I served as negative control without administration of any treatment except plain water ad libitum. Groups II and III served as positive treatment control groups and were administered with IBD intermediate vaccine and cyclophosphamide as immunosuppressive agents respectively. The remaining treatment groups IV to IX were given either cow urine distillate alone or in combination with aqueous polyherbal extract along with intermediate IBD vaccine and cyclophosphamide. Six birds from each experimental group were sacrificed on day 0, 15, 30, 45 and 60 for collection of materials for lymphoblastogenesis study. The assay revealed significant decrease (P
Keywords: Cow urine distillate; Lymphoblastogenesis; Polyherbal extract; Layer chicks